Study on dynamic characteristics of intake system and combustion of controllable intake swirl diesel engine. (1st August 2019) - Wang, Guixin; Yu, Wenbin; Li, Xiaobo; Su, Yanpan; Yang, Rui; Wu, Wentao
Abstract: This paper investigated the intake flow field of a controllable intake swirl diesel engine using computational fluid dynamics (CFD) methodology. It can be observed that the variation of the intake swirl with the opening of the intake baffle shows the two-stage characteristics, while the baffle opening angle of 48° is as a cut-off point. Through the comprehensive analysis of the influence of valve lift and baffle opening angle on flow coefficient, it is concluded that the influence of valve lift on flow coefficient is more sensitive. A mathematical method is used to fit the formula which can calculate the key characteristics of the controllable intake swirl diesel engine. Meanwhile the influence of the swirl ratio on combustion characteristics is investigated. It can be concluded that the swirl ratio has greater influence on the power performance of the diesel engine. When the swirl ratio increases from 0.4 to 1.2, the power performance is increased by 5.79%, and the fuel consumption was also improved. Finally, according to the actual structure of the intake system of diesel engine, a steady-state intake flow test bed was established to verify the accuracy of CFD study of the intake system. Highlights: The swirl ratio of the controllable intake swirl diesel engine has two-stage characteristics. The diesel engine valve lift is more sensitive to the flow coefficient than the intake baffle. Two stage characteristics of the intake swirl is the intrinsic property of a diesel engine. The swirl ratio is more favorable for improving the effective power of a diesel engine.